MDFI is a novel biomarker for poor prognosis in LUAD - Chen, Pengyu; Quan, Zhen; Song, Xueyu; Gao, Zhaojia; Yuan, Kai (Frontiers in Oncology, 2022)
Approximately 85% of lung cancers are non-small cell lung cancers (NSCLC). Lung adenocarcinoma (LUAD) is the main subtype of NSCLC. The incidence and mortality of lung cancer are also increasing yearly. Myod family inhibitor (MDFI) as a transcription factor, its role in lung cancer has not yet been clarified. LUAD data were downloaded from the Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO), analyzed and plotted using the R language. Associations between Clinical information and MDFI expression were assessed using logistic regression analyses to explore the effects of MDFI on LUAD. The overexpression of MDFI in LUAD and its impact on prognosis were further confirmed by two groups of TAMs. In addition, we examined the correlation between MDFI and immune infiltration. To investigate the effect of MDFI on the biological behavior of LUAD tumor cells by GSEA and GO/KEGG analysis. The survival status and somatic mutational characteristics of patients according to MDFI levels were depicted and analyzed.Expression of high MDFI in LUAD tissues via analyzing TCGA dataset (p <0.001). Kaplan-Meier survival analysis indicated a poor prognosis for those patients with LUAD who had upregulated MDFI expression levels (p<0.001). This was also verified by two groups of TAMs (p=0.024). Using logistic statistics analysis, MDFI was identified as an independent predictive factor and was associated with poor prognosis in LUAD (p <0.001, p =0.021). Assessment of clinical characteristics, tumor mutation burden (TMB), and tumor microenvironment (TME) between high- and low-expression score groups showed lower TMB, richer immune cell infiltration, and better prognosis in the low-risk group.This study showed that MDFI was overexpressed in LUAD and was significantly associated with poor prognosis, indicating that MDFI may be used as a potential novel biomarker for the diagnosis and prognosis of LUAD, and is associated with immune infiltration of LUAD, and plays an important role in tumor proliferation and spread. In view of the significant differences in MDFI expression between different biological activities, LUAD patients with MDFI overexpression may obtain more precise treatment strategies in the clinic..